Image Techniques for Identifying Sea-Ice Parameters - Zhang, Qin; Skjetne, Roger (Modeling, Identification and Control: A Norwegian Research Bulletin, 2014)
The estimation of ice forces are critical to Dynamic Positioning (DP) operations in Arctic waters. Ice conditions are important for the analysis of ice-structure interaction in an ice field. To monitor sea-ice conditions, cameras are used as field observation sensors on mobile sensor platforms in Arctic. Various image processing techniques, such as Otsu thresholding, k-means clustering, distance transform, Gradient Vector Flow (GVF) Snake, mathematical morphology, are then applied to obtain ice concentration, ice types, and floe size distribution from sea-ice images to ensure safe operations of structures in ice covered regions. Those techniques yield acceptable results, and their effectiveness are demonstrated in case studies. (c) 2014 Norwegian Society of Automatic Control. Creative Commons Attribution 3.0 Unported (CC BY 3.0) license. See: http://creativecommons.org/licenses/by/3.0/.